Resonancias 2020
DOI: 10.7764/res.2020.47.9
|View full text |Cite
|
Sign up to set email alerts
|

Musical sophistication explains a good deal of cognitive performance. A cross-sectional study of musicians and non-musicians

Abstract: Musical sophistication is a psychometric construct that can be measured both in people with musical training and without training. Through backgrounds related to musical activities in their lifetime, and other indicators referring to their current events, the person’s musical sophistication can be estimated with a relatively high level of reliability (Cronbach’s α =.78). In turn, few studies have covered the relationships between variables of this type and cognitive performance, leaving an area of research wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…We would state that at least two of the three alternative hypotheses of the present study can be accepted: in one of them, we predicted the association between music training and superior audiovisual WM and fluid intelligence and, actually, the group of musicians showed a better performance compared to nonmusicians in both domains. The present results converge with prior studies where music training was associated with superior cognitive abilities (Schellenberg, 2006(Schellenberg, , 2011bDegé et al, 2011;Slevc et al, 2016;Baker et al, 2018;Meyer et al, 2020;Porflitt and Rosas, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…We would state that at least two of the three alternative hypotheses of the present study can be accepted: in one of them, we predicted the association between music training and superior audiovisual WM and fluid intelligence and, actually, the group of musicians showed a better performance compared to nonmusicians in both domains. The present results converge with prior studies where music training was associated with superior cognitive abilities (Schellenberg, 2006(Schellenberg, , 2011bDegé et al, 2011;Slevc et al, 2016;Baker et al, 2018;Meyer et al, 2020;Porflitt and Rosas, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The variables associated with academic performance are located on the axis of musical sophistication in the PCA. This may be consistent, to a degree at least, with the results of Porflitt and Rosas [ 15 , 62 ] in the Chilean context, who reported an association between OMSI result and executive functions. On the other hand, the independence of academic performance from scores in the university transition tests (PDT) and high school grades (NEM) is striking.…”
Section: Discussionsupporting
confidence: 91%
“…When those elements are not fulfilled, this may be reflected in problems of motivation and autonomy [ 42 , 43 ], as well as discomfort and frustration [ 44 ], which ultimately affect academic performance [ 45 ]. Previous research using self-reporting has shown that musical sophistication predicts visual, aural, and creative skills [ 8 ], as well as cognitive performance [ 15 ]. Thus, considering the theoretical background presented, in the present study we expected to find: That first year music students with poor musical backgrounds (measured through the OMSI) face greater difficulties in the educational transition process than their peers, from the perspective of the construct of well-being.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations